Services in the Development Context : A Case Study of India - Prasad, H. Ashok Chandra (England : Institute of Development Studies, 1992)
The paper examines the role of services in the Indian developmental context.
rua 12/06/17
Loans.
Keywords: Services industries; Developing countries; India